In vitro assessment of anti-proliferative effect induced by alpha-mangostin from Cratoxylum arborescens on HeLa cells - El habbash, Aisha I.; Mohd Hashim, Najihah; Ibrahim, Mohamed Yousif; Yahayu, Maizatulakmal; Abd Elmutaal Omer, Fatima; Abd Rahman, Mashitoh; Nordin, Noraziah; Ee, Gwendoline Cheng Lian (PeerJ, 2017)
Natural medicinal products possess diverse chemical structures and have been an essential source for drug discovery. Therefore, in this study, α-mangostin (AM) is a plant-derived compound was investigated for the apoptotic effect on human cervical cancer cells (HeLa). The cytotoxic effects of AM on the viability of HeLa and human normal ovarian cell line (SV40) were evaluated by using MTT assay. Results showed that AM inhibited HeLa cells viability at concentration- and time-dependent manner with IC50 value of 24.53 ± 1.48 µM at 24 h. The apoptogenic effects of AM on HeLa were assessed using fluorescence microscopy analysis. The effect of AM on cell proliferation was also studied through clonogenic assay. ROS production evaluation, flow cytometry (cell cycle) analysis, caspases 3/7, 8, and 9 assessment and multiple cytotoxicity assays were conducted to determine the mechanism of cell apoptosis. This was associated with G2/M phase cell cycle arrest and elevation in ROS production. AM induced mitochondrial apoptosis which was confirmed based on the significant increase in the levels of caspases 3/7 and 9 in a dose-dependent manner. Furthermore, the MMP disruption and increased cell permeability, concurrent with cytochrome c release from the mitochondria to the cytosol provided evidence that AM can induce apoptosis via mitochondrial-dependent pathway. AM exerted a remarkable antitumor effect and induced characteristic apoptogenic morphological changes on HeLa cells, which indicates the occurrence of cell death. This study reveals that AM could be a potential antitumor compound on cervical cancer in vitro and can be considered for further cervical cancer preclinical and in vivo testing.